Perfil de susceptibilidad antimicrobiana y producción de hemolisina de enterobacterias de psitácidos en cautiverio - Trindade, Lenize; Figueira , Paulo Tadeu (Pubvet, 2018)
The practice of getting pets is increasingly inserted in society; this fact is due to the welfare and quality of life that the living with these animals brings to humans. The search for exotic animals has become frequent, with parrots being one of the groups most appreciated for this purpose. However, these birds are likely to transmit pathogens both to man and to other animals, representing a relevant risk factor for public health. The aim of this work was to determine the profile of antimicrobial susceptibility and hemolysin production in enterobacteria isolated from psittacines of captive of bird park in Toledo city Brazil. Escherichia coli positive samples (20% of the analysed sample), previously identified and isolated, were analyzed and performed according to Kirby & Bauer method. Subsequently, virulence factor evaluation was performed by hemolytic activity test (TAH) by sowing the samples in Blood agar, having as a positive control sample of E. coli EHEC and as negative controls a sample of E. coli K12. The interpretation of the values of halos obtained in the antibiogram verified the degree of sensitivity of E. coli samples to antibiotics, where the resistance of the samples to several antibiotics tested was noted. Gamma haemolysis was identified in the TAH test. The determination of the sensitivity profile of strains of E. coli makes even more relevant the concern with microorganism’s pathogenicity that these birds can carry, considering the degree of resistance of these bacteria to the tested antibiotics. This profile also made it possible to know which antimicrobials have a more effective action on the bacteria found, allowing a better understanding of the microbiota of these animals.